Antibacterial Properties of Cow Urine Collected from a Badri Calf - Arya, Mansi; Bora, Shikha; Parveen, Nagma; Melkani, Deepak Chandra; Rawat, Gaurav; Sharma, Netra Pal; Bisht, Satpal Singh (Asian Journal of Biological and Life Sciences)
Background: This study investigates the antibacterial potential of Badri cow urine against various pathogenic bacteria, including Pseudomonas aeruginosa, Aeromonas salmonicida, Escherichia coli, Listeria monocytogenes, and Xanthomonas campestris. Materials and Methods: The urine was collected aseptically from Badri cattle, filtered, and tested using the tube dilution method to determine the Minimum Inhibitory Concentration (MIC) and the agar well diffusion assay to assess the zone of inhibition. Results: MIC values ranged from 15.62 to 125 μL/mL, with E. coli (MTCC 724) showing the lowest MIC at 15.62 μL/µ, indicating high sensitivity and followed by 31.2562 μL/mL, Xanthomonas campestris (ITCCBH0006). The agar well diffusion assay revealed inhibition zones ranging from 7.00 to 24.00 mm, with E. coli (MTCC 40) and Xanthomonas campestris (ITCCBH0006) exhibiting the largest zones at 20.00 mm and 19.00 mm, respectively. Conclusion: Notably, cow urine demonstrated significant antibacterial efficacy against Xanthomonas campestris, a plant pathogen resistant to the positive control, ampicillin. These findings align with previous studies and highlight cow urine’s potential as a natural antimicrobial agent, suggesting its use as an alternative therapeutic strategy to combat antibiotic resistance and support sustainable disease management.
Keywords: Antibacterial; Badri Cow; Urine; MIC; well Diffusion.